2004
DOI: 10.1128/jvi.78.14.7813-7817.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biased Hypermutagenesis Associated with Mutations in an Untranslated Hairpin of an RNA Virus

Abstract: The mutation frequency of Turnip crinkle virus can increase 12-fold without inducing error catastrophe. Lesions in a hairpin repressor frequently reverted and led to second-site alterations biased for specific mutations. These results suggest that the hairpin may also function as an RNA chaperone to properly fold the RNA-dependent RNA polymerase.Turnip crinkle virus (TCV), a member of the genus Carmovirus in the family Tombusviridae, has been used as a model for identifying cis-acting elements important for RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
16
2
1
Order By: Relevance
“…We have recently determined that mutating these adenylates suppresses specific RdRp binding to the 39 region of the virus, which could account for the more severe effect of m49 on virus accumulation (M. Young and A. E. Simon, unpubl.). While the H5 mutations had no effect on translation and deletion of H5 only reduced F1 ribosome binding by twofold, previous mutations in H5 (McCormack and Simon 2004) and m23 (this report) significantly lowered TCV accumulation in protoplasts. We previously demonstrated that accumulation of nontranslated satC requires maintenance of H5 structure and the LSL adenylates (Zhang et al 2004;Zhang and Simon 2005).…”
Section: Role Of the 39 Internal Tss In Translational Enhancementmentioning
confidence: 81%
See 2 more Smart Citations
“…We have recently determined that mutating these adenylates suppresses specific RdRp binding to the 39 region of the virus, which could account for the more severe effect of m49 on virus accumulation (M. Young and A. E. Simon, unpubl.). While the H5 mutations had no effect on translation and deletion of H5 only reduced F1 ribosome binding by twofold, previous mutations in H5 (McCormack and Simon 2004) and m23 (this report) significantly lowered TCV accumulation in protoplasts. We previously demonstrated that accumulation of nontranslated satC requires maintenance of H5 structure and the LSL adenylates (Zhang et al 2004;Zhang and Simon 2005).…”
Section: Role Of the 39 Internal Tss In Translational Enhancementmentioning
confidence: 81%
“…While mutations in the H5 LSL (Fig. 3A, m23,m38) did not affect translation, virus containing these mutations accumulated to 31% and 88% of wt levels, respectively, reflecting a role for some of the H5 LSL adenylates (e.g., A3978 [m23]) in replication (McCormack and Simon 2004;Zhang et al 2006c). …”
Section: In Vivo Mapping Of the Tcv 39 Translational Enhancermentioning
confidence: 99%
See 1 more Smart Citation
“…Using in vitro and in vivo approaches, the Pr was previously identified as the satC core promoter (Song and Simon 1995;Carpenter and Simon 1998). H5, also critical for satC and TCV replication (McCormack and Simon 2004;Zhang et al 2004a;Zhang and Simon 2005), contains a large symmetrical internal loop (LSL) whose sequence is highly conserved among related carmoviruses (Zhang et al 2004b). A combination of approaches including single-site mutagenesis, in vivo genetic selection (SELEX), and sequence replacements with analogous segments from the related carmovirus Cardamine chlorotic fleck virus (CCFV) indicates that both specific sequence and structural features throughout H5 are necessary for robust satC accumulation in plants and protoplasts (Zhang et al 2004a;Zhang and Simon 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A los elementos cis que intervienen en la replicación se les atribuyen diversas funciones, entre ellas: (1) participar en la formación de los complejos replicativos Wu et al, 2009], (2) actuar como promotores de la replicación promoviendo la síntesis de novo de la cadena complementaria [Kim et al, 2000;Kao et al, 2001], (3) regular la síntesis asimétrica de las cadenas de polaridad positiva y negativa [Ball, 2007], (4) intervenir en la transcripción de los distintos sgRNAs, si procede [Kim & Hemenway, 1999;Grdzelishvili et al, 2005] y, (5) funcionar como chaperonas de RNA [McCormack & Simon, 2004]. como mRNA permitiendo la traducción de las replicasas virales.…”
Section: Moldes Virales Requerimientos Estructurales Y De Secuenciaunclassified